VARIOUS IMPACTS CAUSED BY THE GENOCIDE IN RWANDA: QUOTED FROM KOMPAS MEDIA COVERAGE - Muhammad Dandy Alif Pratama; Nur’annafi Farni Syam Maella; Farida Farida (Journal of Economic, Bussines and Accounting (COSTING), 2025)
In 1994, Rwanda experienced a genocide that resulted in hundreds of thousands of casualties at that time. There are two major tribes in this country, namely the Tutsi tribe and the Hutu tribe. The conflict between these two tribes was what initiated the genocide in Rwanda. As a media outlet, Kompas explains in depth how this genocide has caused significant impacts in Rwanda, namely social, legal, and political crises. Through qualitative methods, this article will explain the causes of how this genocide occurred, the process of post-genocide reconciliation in Rwanda, and how Rwanda rebuilt and transformed its country.